Challenges and prospects of transboundary river water conservation and watershed protection in Ethiopia: The case of the upper Blue Nile - Emiru Gemechu Kedida; Yacob Arsano (Heliyon, 2024)
This article aims to present the challenges and prospects of transboundary river water conservation and watershed protection in the Upper Blue Nile basin. The River Nile Basin embraces eleven countries shaping their diverse environments and playing a vital role in the livelihoods of its inhabitants. Within this context sharing and managing the River Nile water resources has been a persistent challenge and a potential source of conflict. The Blue Nile River is shared by Ethiopia, Sudan and Egypt and for the latter it is the life artery as the majority of the water reaching Egypt comes from the Blue Nile. Only Egypt and Sudan have an agreement to share the water and there is a need to revisit this mode of resource use based on water allocation among the River Nile countries and especially for the Blue Nile. Nevertheless, these issues have not been resolved and have exacerbated by the commencement and near operation of the GERD. Another important aspect dealt with in this article is the conservation and watershed protection. The study used a qualitative research approach, and data were collected through key informant interviews. Different relevant secondary sources are also consulted. The data were analyzed based on a thematic analysis approach. The key finding of this study was that, despite the Ethiopian unilateral intervention inadequacy to deal with the problem of environmental degradation and water conservation in the Blue Nile Basin neither Ethiopia nor regional institutions like ENTRO attempted to shed light on the impacts of this problem if remained unaddressed. Moreover, Ethiopia and regional actors are void of designing a clear road map to overcome the cloud of mistrust and struggle to dominate the Nile water use which undermined hope for joint action against the common problem that jeopardize the interests of all the basin states. On the other hand the Ethiopian effort to safeguard the shared Nile water resource in the Blue Nile basin yield modest results it may encourage the basin countries to cooperate over the use and management of the Nile water. Hence, the inadequacy of Ethiopia's sole effort to conserve and protect the Upper Nile watershed calls for Ethiopian water management policy and water diplomacy to push for the collaboration of the downstream states as the threats to the Nile water supply are common threats to all Nile basin states' national water security.